Penerapan sistem informasi manajemen perbankan syariah berbasis e-banking syariah - agusty, rizal ubaidilbar (Maliki Interdisciplinary Journal, 2024)
Developments in the modern era have resulted in rapid advances in technology, especially the internet, which has become an inseparable part of everyday life. In the sharia banking sector, collaboration with information technology has provided a special information system that simplifies transaction processes, including e-banking services. E-banking, which includes internet banking, SMS/m-banking, telephone banking, and ATM, provides convenience and comfort for customers in carrying out various banking transactions. However, keep in mind that there are risks associated with using e-banking, so careful security measures are necessary. Apart from that, sharia banking also highlights the importance of four key strategies to maintain competitiveness, namely the formation of SDI, market expansion, developing diverse products, and increasing the use of modern IT systems. Thus, management information systems and e-banking play a very important role in increasing efficiency and convenience in banking transactions, while Islamic banking strategies aim to expand services and maintain their competitive position.